Assessment of Risks of Investment and Construction Activities: Russian Practice - OSADCHAYA, N.A.; MURZIN, A.D.; TORGAYAN, E.E. (Journal of Advanced Research in Law and Economics; Vol 8 No 2 (2017): Volume VII, Issue 2(24), Spring 2017, 2017)
The article deals with the study of assessment of risks in the Russian practice of investment and construction activities for the purpose of identification of the national specifics and distinctive aspects. The specific risks of investment and construction activities are described on the basis of the standard analytical methods, their generalized classification is given, possible risks are checked against the stages of the investment and construction project life cycle, factors of risks of the construction organizations are grouped, and methods of analysis and risk assessment that are used in managing investment and construction activities in Russia are reviewed. A real investment and construction project for the construction of a multifunctional complex of a business hotel with apartments in Rostov-on-Don by the 2018 FIFA World Cup was reviewed as an illustration of the Russian practice of the risk assessment process. 5 options of investment evaluation were modeled based on materials of the project, and risks of receiving less profit due to changes in the amount of borrowed capital, the timing of supply of materials and equipment, as well as the lending rate were assessed. Following the results of the discussion of the study materials, the authors summarized the problems of investment and construction activities and risk management of investment and construction projects in Russia, as well as developed a complex structure of the system of managing the investment risks of construction companies, the practical application of which will allow to enhance the sustainability of construction companies on the Russian market.